Informing resilience building: FAO's Surveillance Evaluation Tool (SET) Biothreat Detection Module will help assess national capacities to detect agro-terrorism and agro-crime - Gisela Vasconcelos Gioia; Gaël Lamielle; Ryan Aguanno; Ihab ElMasry; Béatrice Mouillé; Cristian De Battisti; Angélique Angot; Fanny Ewann; Adrien Sivignon; Daniel Donachie; Orr Rozov; Étienne Bonbon; et al. (BMC, 2021)
Abstract Attacks using animal pathogens can have devastating socioeconomic, public health and national security consequences. The livestock sector has some inherent vulnerabilities which put it at risk to the deliberate or accidental spread of disease. The growing concern of countries about the risks of agro-terrorism and agro-crime has led to efforts to prepare against potential attacks. One recent international effort is the launch of a joint OIE, FAO and INTERPOL project in 2019 to build resilience against agro-terrorism and agro-crime targeting animal health with the financial support of the Weapons Threat Reduction Programme of Global Affairs Canada. Given the importance of strong animal health surveillance systems for the early and effective response to agro-terrorism and agro-crime, the project will use the FAO Surveillance Evaluation Tool (SET) and its new Biothreat Detection Module to evaluate beneficiary countries' capacities to detect criminal or terrorist animal health events. This paper presents the development of the new SET Biothreat Detection Module and how it will be used to evaluate surveillance for agro-terrorism and agro-crime animal disease threats. The module will be piloted in early 2021 and, once finalized, will be used by beneficiary countries of the joint OIE-FAO-INTERPOL project. Results from evaluations using SET and its Biothreat Detection Module are expected to provide a baseline from which countries can build targeted capacity for animal disease surveillance including early detection and investigation of potential terrorist or criminal events involving zoonotic and non-zoonotic animal pathogens.